Nasal High-flow Therapy during Neonatal Endotracheal Intubation. Issue 4 (21st December 2022) - Hodgson, D.; Owen, L.; Kamlin, C.; Roberts, C.; Newman, S.; Francis, K.; Donath, S.; Davis, P.; Manley, B.
Abstract : ( N Engl J Med . 2022;386:1627–1637) Fetal intubation attempts frequently have low success rates and take longer versus international guidelines, especially when performed by inexperienced operators. This results in increased rates of intraventricular hemorrhage and airway injury in vulnerable neonatal patients. Transnasal humidified rapid insufflation ventilatory exchange, the use of nasal high-flow therapy (HFT) to aid respiratory support, is a proven useful aid in older children and adult intubation in a variety of circumstances. However, the relationship between neonates and nasal HFT during intubation was previously untested. This study examined the success rates of nasal HFT use during intubation against those not receiving HFTs. This study defined initial intubation attempt as the insertion length past the infant's lips of the laryngoscope blade and successful intubation as the presence of carbon dioxide expiration after the placement of an endotracheal tube.